The Backbone Structure of Audience Networks: A New Approach to Comparing Online News Consumption Across Countries. (3rd April 2019) - Majó-Vázquez, Sílvia; Nielsen, Rasmus K.; González-Bailón, Sandra
Abstract : Measures of audience overlap between news sources give us information on the diversity of people's media diets and the similarity of news outlets in terms of the audiences they share. This provides a way of addressing key questions like whether audiences are increasingly fragmented. In this article, we use audience overlap estimates to build networks that we then analyze to extract the backbone—that is, the overlapping ties that are statistically significant. We argue that the analysis of this backbone structure offers metrics that can be used to compare news consumption patterns across countries, between groups, and over time. Our analytical approach offers a new way of understanding audience structures that can enable more comparative research and, thus, more empirically grounded theoretical understandings of audience behavior in an increasingly digital media environment.